2020
DOI: 10.31557/apjcp.2020.21.6.1623
|View full text |Cite
|
Sign up to set email alerts
|

Associations of the -238(G/A) and -308(G/A) TNF-α Promoter Polymorphisms and TNF-α Serum Levels with the Susceptibility to Gastric Precancerous Lesions and Gastric Cancer Related to Helicobacter pylori Infection in a Moroccan Population

Abstract: Objective: Helicobacter pylori (H. pylori) induces the production of tumor necrosis factor-alpha (TNF-α), which is closely related to a gastric epithelial injury. TNF-α gene polymorphism and TNF-α serum levels are associated with various malignant conditions. Identification of the ideal marker for gastric cancer (GC) is still the leading aim of several trials. Physio-pathological considerations of GC led us to investigate the ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 41 publications
1
5
1
Order By: Relevance
“…Combining the NM and CG groups also revealed a lower TNF-α level in patients with FHGC than those without (12.5 ± 14.2 vs. 31.0 ± 36.3 pg/ml; p = 0.003). According to the herein performed extensive literature review (Supplementary Table 1), our results are not in line with many studies [ 5 7 ] which have reported relatively higher serum levels of TNF-α in GC patients, as compared to healthy controls. However, our results are consistent with two other studies indicating a lower concentration of TNF-α in GC patients [ 8 , 9 ] .…”
Section: Resultscontrasting
confidence: 99%
“…Combining the NM and CG groups also revealed a lower TNF-α level in patients with FHGC than those without (12.5 ± 14.2 vs. 31.0 ± 36.3 pg/ml; p = 0.003). According to the herein performed extensive literature review (Supplementary Table 1), our results are not in line with many studies [ 5 7 ] which have reported relatively higher serum levels of TNF-α in GC patients, as compared to healthy controls. However, our results are consistent with two other studies indicating a lower concentration of TNF-α in GC patients [ 8 , 9 ] .…”
Section: Resultscontrasting
confidence: 99%
“…Several studies on Moroccan and Brazilian patients found no association between this polymorphism and gastric pathologies, which is consistent with our data [42,43]. On the other hand, TNF-α-308 polymorphism was considered a risk factor for GC in Caucasians and western populations [44,45].…”
Section: Discussionsupporting
confidence: 92%
“…The genetic predisposition to cancers has been demonstrated through several studies and is still a subject of interest and scientific research [ 11 , 13 , 19 ]. Serum levels of sTNFR1 are used as a predictive marker of multifactorial inflammatory disorders and cancers [ 12 , 17 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The PCR products were checked out in 1.5% agarose gel electrophoresis and purified using 1 μ L of exonuclease (Thermo Scientific), 1 μ L of alkaline phosphatase (Promega), and 5 μ L of PCR product and incubated at 37°C for 15 minutes and 80°C for 15 minutes. The DNA sequencing conditions were carried out based on the method as previously described [ 19 ]. The DNA sequences were read by an Applied Biosystems 377 DNA sequencer and analyzed using the BIOEDIT software package.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation